2013
DOI: 10.1186/1475-2891-12-46
|View full text |Cite
|
Sign up to set email alerts
|

Effects of indigestible carbohydrates in barley on glucose metabolism, appetite and voluntary food intake over 16 h in healthy adults

Abstract: BackgroundRecent knowledge in animals suggests that gut microbial metabolism may affect host metabolism, including appetite regulating hormones. The aim of the present study was to evaluate the potential effects of a whole grain barley kernel product, rich in intrinsic indigestible carbohydrates (dietary fibre and resistant starch), on markers of metabolism and appetite regulation in healthy subjects.MethodsBoiled barley kernels (BK) or white wheat bread (WWB; reference) were provided as late evening meals to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 57 publications
(63 reference statements)
3
72
1
Order By: Relevance
“…Intervention studies often have small numbers of subjects and show the benefits of ingestion of a specific whole grain, such as oats or rye, but not necessarily a mixture of whole grains or brown rice (37)(38)(39)(40). Even large randomized intervention trials (41), such as one with healthy overweight subjects in the United Kingdom, have not shown improvements in markers of heart disease with increased intake of whole grain foods compared with usual intake.…”
Section: Health Benefits Of Whole Grainsmentioning
confidence: 99%
“…Intervention studies often have small numbers of subjects and show the benefits of ingestion of a specific whole grain, such as oats or rye, but not necessarily a mixture of whole grains or brown rice (37)(38)(39)(40). Even large randomized intervention trials (41), such as one with healthy overweight subjects in the United Kingdom, have not shown improvements in markers of heart disease with increased intake of whole grain foods compared with usual intake.…”
Section: Health Benefits Of Whole Grainsmentioning
confidence: 99%
“…Dietary interventions are thus a potential tool to modulate gut microbiota and further impact host health (18,19). Previous studies have shown that resistant starch (rich in nonstarch polysaccharides) improved glucose tolerance in healthy subjects with a normal body mass index (20,21) and provided evidence of a link between colonic fermentation and glucose metabolism (20). However, to date, little information is available about the impact of KF feed consumption on the gut microbiota of pregnant females and the correlation between gut microbiota and metabolic parameters after dietary KF supplementation.…”
mentioning
confidence: 99%
“…However, other studies have informed researchers about the mechanisms underlying the effects of RS on oxidative stress. Some proposed mechanisms for prebiotics antioxidant effects include the scavenging ability of reactive oxygen species (ROS) [32] , SCFAs [33] , reduction of inflammation and endotoxin [34] , a change in microflora toward Lactobacilli which contain antioxidants [35] , suppression of CD11c expression in adipose tissue [36] and reduction of the levels of FFAs [37] .…”
mentioning
confidence: 99%